Mortality from bladder cancer in dyestuff workers exposed to aromatic amines: A 73-year follow-up - Ciocan, Catalina; Godono, Alessandro; Franco, Nicolò; La Vecchia, Carlo; Negri, Eva; Boffetta, Paolo; Pira, Enrico (La Medicina del Lavoro, 2022)
Objective. To update the analysis of mortality of a cohort of dyestuff workers, in Northern Italy, heavily exposed to carcinogenic aromatic amines.Methods. We updated to 2018 overall and cause-specific mortality in a cohort of 590 male workers heavily exposed to carcinogenic aromatic amines in a dyestuff factory from 1922 to 1972. Workers were censored at age 85. Expected cases for the period 1946-2018 were computed using Piedmont mortality rates and standardized mortality ratios (SMR) were computed.Results. Between 1946 and 2018, 470 deaths were reported. The overall SMR was 1.59 (95% confidence interval [CI] 1.45-1.74) and SMR from all cancers was 2.05 (95% CI = 1.77-2.37); Compared to a previous report, there were 4 additional  deaths from bladder cancer,  for a total of 60 deaths compared  with 4.0 expected  (SMR 14.86, 95% CI 11.34-19.12).The SMR for bladder cancer increased with younger age at first exposure  and longer duration of exposure, while it  decreased with time since last exposure, albeit it was still 3.5, 30 or more years since last exposure. An increased risk was observed among workers exposed to fuchsine or ortho-toluidine (SMR=16.3; 95% CI = 6.0-35.5).Conclusions. This 73 year follow up confirms the results from previous analyses, with an increased overall mortality and, an increased mortality from all cancers and especially for bladder cancer. The excess risk of bladder cancer persisted several decades after stopping exposure.